Multiple Land Rights Certificate Case Settlement Review of Land Registration - Daniel Yudi Christanto; Anis Mashdurohatun (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The research objective is to know and analyze completion of Multiple Land Rights Certificate in Banyumas Regency. To find out and analyze problems in resolving the case of double certified land rights in Banyumas Regency, and To find out and analyze solution against Settlement of double certified land rights cases in Banyumas Regency.This research is a qualitative research with a normative juridical approach. Based on the results of research and discussion it can be seen that